Competitive queueing systems with comparative rating dependent arrivals - A. N. Dudin; S. A. Dudin; O. S. Dudina; K. E. Samouylov (Operations Research Perspectives, 2020)
We consider the joint operation of two multi-server queueing systems. Both systems provide the same type of service and compete for customers. It is assumed that the first system is controlled by ourselves while the second one is controlled by our competitor. The arriving customers are shared between the systems depending on the comparative rating of our system. The stationary behavior of the considered model under the fixed parameters of both systems and the fixed mechanism of calculation of the rating is described by a continuous-time multi-dimensional Markov chain. The stationary distribution of this Markov chain is computed. Expressions for the key performance measures of the systems are derived. Obtained results provide an opportunity to analyse possible consequences of various managerial actions aiming to maximize the profit of our system. A numerical experiment illustrates the application of the results for making a decision about the rationality of establishing and maintaining a service system while an alternative system providing the same type of service already exists.
Keywords: 330; Queueing systems; Competition; Comparative rating; Marked Markovian arrival process; Optimization